Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.aap.2016.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Drivers anticipate lead-vehicle conflicts during automated longitudinal control: Sensory cues capture driver attention and promote appropriate and timely responses

Abstract: Adaptive Cruise Control (ACC) has been shown to reduce the exposure to critical situations 12 by maintaining a safe speed and headway. It has also been shown that drivers adapt their visual behavior 13 in response to the driving task demand with ACC, anticipating an impending lead vehicle conflict by 14 directing their eyes to the forward path before a situation becomes critical. The purpose of this paper is 15 to identify the causes related to this anticipatory mechanism, by investigating drivers' visual beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
33
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 28 publications
4
33
0
Order By: Relevance
“…1) The effect of automation: The significant decrease of PRC (eyes on path) when using ACC+LKA compared to manual driving (Fig. 7a) is consistent with previous studies on the real-world effect of ACC [37], [39], [40]. The lower PRC is interpreted as a symptom of a reduction in driving task demand when using vehicle automation, because of vehicle allocation of some of the control tasks-longitudinal and lateral control.…”
Section: B Visual Response To Driving Contextsupporting
confidence: 86%
See 3 more Smart Citations
“…1) The effect of automation: The significant decrease of PRC (eyes on path) when using ACC+LKA compared to manual driving (Fig. 7a) is consistent with previous studies on the real-world effect of ACC [37], [39], [40]. The lower PRC is interpreted as a symptom of a reduction in driving task demand when using vehicle automation, because of vehicle allocation of some of the control tasks-longitudinal and lateral control.…”
Section: B Visual Response To Driving Contextsupporting
confidence: 86%
“…The lower PRC is interpreted as a symptom of a reduction in driving task demand when using vehicle automation, because of vehicle allocation of some of the control tasks-longitudinal and lateral control. Note that Morando, Victor and Dozza's 2016 work [39] showed that this PRC reduction effect occurs in steadystate driving with ACC, and that glances do return on-path in response to vehicle deceleration regulation if the lead vehicle brakes. A difference in PRC in the off-path glance distribution between manual and ACC+LKA driving was also expected.…”
Section: B Visual Response To Driving Contextmentioning
confidence: 97%
See 2 more Smart Citations
“…Prior studies on vision and driving using naturalistic driving methods have not examined visual risk factors for crash and near-crash events. 1120 Therefore, the purpose of this study was to examine the association between visual sensory and visual-cognitive function and rates of crash or near-crash involvement among older drivers using a naturalistic study design.…”
mentioning
confidence: 99%